Answer:
Explanation:
Given
Person on earth can jump to a height [tex]s=0.6\ m[/tex]
initial velocity is u
using
[tex]v^2-u^2=2as[/tex]
where v=final velocity
u=initial velocity
a=acceleration
s=displacement
final velocity is zero
[tex]s=\frac{u^2}{2g}[/tex]
[tex]0.6=\frac{u^2}{2g}-----1[/tex]
On moon surface acceleration due to gravity is \frac{1}{6}[/tex] th of earth gravity
so height attained is given by
[tex]h=\frac{u^2\times 6}{2\cdot g}-----2[/tex]
divide 1 and 2 we get
[tex]h=6\times 0.6=3.6\ m[/tex]